1986
DOI: 10.1128/jcm.24.1.141-142.1986
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a rapid colorimetric method for identification of pathogenic Neisseria

Abstract: A rapid colorimetric method for the identification of pathogenic Neisseria (Identicult-Neisseria; Scott Laboratories, Inc.) based on P-galactosidase, y-glutamylaminopeptidase, and y-prolylaminopeptidase is described. Ail 82 clinical isolates of Neisseria gonorrhoeae, 9 clinical isolates of N. meningitidis, and 5 clinical isolates of N. lactamica were correctly determined to the species level, as were 4 isolates of Branhamella catarrhalis. Reactions were prompt and easily interpreted. The system should be extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The production of hydroxyprolylaminopeptidase by N. cinerea, but not by B. catarrhalis, is of possible differential value (147,177). This enzyme was produced by all N. gonorrhoeae strains examined (84,147,150) and by various percentages of N. meningitidis (84,147,177).…”
Section: Identification and Biochemical Characteristics Of B Catarrhmentioning
confidence: 94%
See 1 more Smart Citation
“…The production of hydroxyprolylaminopeptidase by N. cinerea, but not by B. catarrhalis, is of possible differential value (147,177). This enzyme was produced by all N. gonorrhoeae strains examined (84,147,150) and by various percentages of N. meningitidis (84,147,177).…”
Section: Identification and Biochemical Characteristics Of B Catarrhmentioning
confidence: 94%
“…Various commercial enzyme substrate kits for rapid tests have been described (94,150,155,177,212,233,315). Unfortunately, some rapid tests yield only negative reactions for B. catarrhalis or, worse, false identifications (40,94,109,233).…”
Section: Stages In the Identification Processmentioning
confidence: 99%
“…meningitidis, five N. lac tamica, four Mor. catarrhalis) Hosmer et al (1986) reported loo'% correlation between the Neisseria-Identicult, fermentation tests on Columbia agar slants and the Phadebact Monoclonal GC test. Sperry et al (1986) found 97% correlation between the Neisseria-Identicult and MNYC from a total of 104 isolates (54 N .…”
Section: Discussionmentioning
confidence: 99%
“…Methods for the identification of Neisseria spp. include carbohydrate degradation tests (8,13), chromogenic enzyme substrate tests (6,7,16,17), and combinations of these two approaches (14,15). Conventional procedures use cystinetryptic digest agar (CTA) base medium with added carbohydrates and may require prolonged incubation for some isolates before results are available (13).…”
mentioning
confidence: 99%
“…Most recently, identification methods with specific chromogenic enzyme substrates have become available for rapid identification of Neisseria spp. that grow on selective medium (i.e., N. gonorrhoeae, N. meningitidis, and N. lactamica) (6,7,14,16,17). These systems also provide a presumptive identification of Branhamella catarrhalis, an organism of recognized clinical importance that can also be occasionally recovered on selective medium (e.g., modified Thayer-Martin [MTMI and Martin-Lewis agars) (4; G. V. Doern, Clin.…”
mentioning
confidence: 99%